2014
DOI: 10.5656/ksae.2013.11.1.061
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Host Plants of Cerambycidae (Coleoptera: Chrysomeloidea) with new Host Records for Fourteen Cerambycids, Including the Asian Longhorn Beetle (Anoplophora glabripennis Motschulsky), in Korea

Abstract: A revised checklist of host plants for 181 species belonging to 103 genera in six subfamilies of Cerambycidae (Coleoptera: Chrysomeloidea) in Korea is provided on the basis of the results of field surveys and literature review. A total of 14 new cerambycid-host associations are confirmed and the Manchurian striped maple, Acer tegmentosum Maxim. (Aceraceae), is listed as a new host of the Asian longhorn beetle, Anoplophora glabripennis (Motschulsky). The names of more than 170 host plants species belonging to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…This highlights the need to analyse material and their composites from infested trees and beetles (from these particular trees), for a better understanding of which parts of the feed gets laid down into the exoskeleton. The research group of Lim et al prepared a review of cerambycid species found on host trees in Korea, in particular on Ulmaceae, Pinaceae, Fagaceae and Betulaceae (more than 23%). Straw et al assessed the infested trees in Kent (UK) and noted sycamore, Acer pseudoplatanus L., as the most attacked species.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need to analyse material and their composites from infested trees and beetles (from these particular trees), for a better understanding of which parts of the feed gets laid down into the exoskeleton. The research group of Lim et al prepared a review of cerambycid species found on host trees in Korea, in particular on Ulmaceae, Pinaceae, Fagaceae and Betulaceae (more than 23%). Straw et al assessed the infested trees in Kent (UK) and noted sycamore, Acer pseudoplatanus L., as the most attacked species.…”
Section: Discussionmentioning
confidence: 99%
“…(Zhang et al 2017). The larvae eat food in the cortex and xylem of the branches and the tunnel is irregular and filled with dung debris, which weakens the trees (Lim et al 2014;Zhang et al 2017). Mitochondrial genome sequences are essential for a deeper understanding of the evolution of Cerambycidae and identification of larva species (Liu et al 2018;Wang and Tang 2018;Wang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Bambusa spp., Chimonobambusa tumidissinoda, Dendrocalamus strictus, Indosasa crassiflora, Phyllostachys spp., Sinobambusa gibbosa, Sinocalamus spp (Mori and Arai 1979,. Hill 2008, Lim et al 2014 …”
mentioning
confidence: 99%